Peran Psikolinguistik dalam Mengoptimalkan Pembelajaran Bahasa Arab di Era Digital - Syafruddin, Lisa; Darmawati (Shaut al Arabiyyah, 2025)
There are many things we need to pay attention to in psycholinguistic studies, starting from the concept and role, challenges and opportunities in learning Arabic in the digital era, as well as its main role in language learning. The aim of this research is to understand the concept and role of psycholinguistics in language learning, find out the challenges and opportunities for learning Arabic in the digital era, and find out the role of psycholinguistics in optimizing language learning. This research approach uses descriptive qualitative with a literature study or literature review method, which is carried out by collecting and analyzing various relevant literature, in the form of books, journals, articles and previous research. The results obtained are; 1) the concept and role of psycholinguistics in language learning can contribute significantly to improving the quality of language learning. 2) challenges in learning Arabic in the digital era, namely the differences between Indonesian and Arabic, curriculum problems, and sociological problems. The opportunity is to be able to develop quality and interesting digital learning materials, access that is more interactive and fun, increase motivation and enthusiasm for learning. 3) The main role of psycholinguistics in language learning is being able to understand the language learning process, developing communication skills, acquiring language, and being able to overcome problems in language skills.